Nearshore subtidal community response during and after sediment disturbance associated with dam removal - Rubin, Stephen P.; Foley, Melissa M.; Miller, Ian M.; Stevens, Andrew W.; Warrick, Jonathan A.; Berry, Helen D.; Elder, Nancy E.; Beirne, Matthew M.; Gelfenbaum, Guy (Frontiers in Ecology and Evolution, 2023)
Sediment disturbances from sources such as landslides and river inputs affect the community composition of marine ecosystems. Dam removal is a relatively new and unstudied source of sediment to coastal ecosystems. The two dam removals on the Elwha River between 2011 and 2014 resulted in more than 14 million tonnes of sediment being delivered to the Strait of Juan de Fuca. This paper provides a rare, long-term study focused on the response and recovery of a nearshore subtidal community to an extended sediment disturbance caused by dam removal. The paper highlights two trajectories of response based on the type of sediment disturbance (burial or high turbidity), as well as the response and recovery of three different species assemblages, algae, benthic invertebrates, and fish. This paper also explores how additional stressors-sea star wasting syndrome and a marine heat wave-affected recovery trajectories, providing important context for how ecosystems respond to and recover from multiple stressors.